A combined theoretical and experimental study of the structure and vibrational adsorption, vibrational circular dichroism, Raman and Raman optical activity spectra of the L-histidine zwitterion - Deplazes, Evelyne; Van Bronswijk, Wilhelm; Zhu, F.; Barron, L.; Ma, S.; Nafie, L.; Jalkanen, Karl (Springer Berlin, 2007)
A combined theoretical and experimental study of the vibrational absorption (VA)/IR, vibrational circular dichroism (VCD), Raman and Raman optical activity (ROA) spectra of l-histidine in aqueous solution has been undertaken to answer the questions (i) what are the species present and (ii) which conformers of the species are present under various experimental conditions. The VA spectra of l-histidine have been measured in aqueous solution and the spectral bands which can be used to identify both species (cation, zwitterion, anion) and conformer of the species have been identified and subsequently used to identify the species (zwitterion) and conformer (gauche minus minus, gauche minus plus for the side chain dihedral angles) present in solution at pH 7.6. The VCD spectral intensities have been used subsequently in combination with further theoretical studies to confirm the conclusions that have been arrived at by only analyzing the VA/IR spectra. Finally a comparison of measured Raman and ROA spectra of l-histidine with Raman and ROA spectral simulations for the conformers and species derived from the combined VA/IR and VCD experimental and theoretical work is presented as a validation of the conclusions arrived at from VA/IR and VCD spectroscopy. The combination of VA/IR and VCD with Raman and ROA is clearly superior and both sets of experiments should be performed.